Compliance and outcomes after implementation of an enhanced recovery surgical protocol in older women undergoing pelvic reconstructive surgery. Issue 11 (November 2020) - Panza, Joseph; Prescott, Lauren; Sorabella, Laura; Dumas, Susan; Helou, Christine; Adam, Rony
The aim of this study is to evaluate compliance and outcomes with implementation of an enhanced recovery surgical protocol in older women undergoing pelvic reconstructive surgery. This is a retrospective cohort study of women undergoing pelvic reconstructive surgery after implementation of the pathway over a 12-month period. Overall compliance was defined as a categorial variable requiring adherence to all of the selected bundle components in patients <65 years old compared to those ≥65. Intraoperative and 30-day postoperative complications were also compared and were reviewed by organ system, these were categorized using the Clavien-Dindo Classification system. There was no significant difference in overall compliance in patients <65 compared to ≥65. Factors that increased compliance in patients ≥65 include laparotomy, hysterectomy, hyperlipidaemia, time after implementation of the protocol and primary surgeon. There was an increase in compliance from 19% to 77% over the 12-month study period. Intra and postoperative complications were similar between the two groups. Enhanced recovery in older patients undergoing pelvic reconstructive surgery is feasible with similar rates of compliance and complications compared to younger patients. Compliance with the protocol increases as time after implementation of the protocol increases in all patients.